Seasonal response of grasslands to climate change on the Tibetan plateau - Yu H; Xu, Jianchu; Okuto E; Luedeling, Eike (Public Library of Science, 2012)
Shortening of the growing season despite a longer thermally favorable period implies that vegetation on the Tibetan Plateau is unable to exploit additional thermal resources availed by climate change. Ecosystem composition may no longer be well attuned to the local temperature regime, which has changed rapidly over the past three decades. This apparent lag of the vegetation assemblage behind changes in climate should be taken into account when projecting the impacts of climate change on ecosystem processes.